Freeze Damage of Carinata Grown in the Southeastern US: SS-AGR-420/AG420, rev. 07/2021 - Mulvaney, Michael J.; Bashyal, Mahesh; Iboyi, Joseph; Seepaul, Ramdeo; Devkota, Pratap; Small, Ian; Wright, David (EDIS, 2021)
This publication serves as a guide to assess freeze damage and discuss management issues related to freeze damage of carinata in the southeastern United States. Written by Michael J. Mulvaney, Mahesh Bashyal, Joseph E. Iboyi, Ramdeo Seepaul, Pratap Devkota, Ian Small, and David Wright, and published by the UF/IFAS Agronomy Department, revised July 2021.